Find the sum of (5x3 + 3x2 - 5x + 4) and (8x3 -5x2 + 8x + 9).

s

jeifunk|Points 74153|

= 25x^4 + 35x^2 - 35x^2 - 49;

= 25x^4 - 49

Question

Asked 7/27/2016 3:23:41 PM

Updated 7/27/2016 9:21:00 PM

3 Answers/Comments

Flagged by jeifunk [7/27/2016 9:19:26 PM], Edited by jeifunk [7/27/2016 9:21:00 PM], Unflagged by jeifunk [7/27/2016 9:21:00 PM]

Rating

3

(9x^2 - 18x - 7) ÷ (3x + 1)

= (3x + 1)(3x - 7)/ 3x + 1

= 3 - 7

= (3x + 1)(3x - 7)/ 3x + 1

= 3 - 7

Added 7/27/2016 9:13:03 PM

This answer has been confirmed as correct and helpful.

3

2(x - 4) + 7(x + 2)

= (2x + 7x) + (-8 + 14)

= 9x + 6

= (2x + 7x) + (-8 + 14)

= 9x + 6

Added 7/27/2016 9:13:53 PM

This answer has been confirmed as correct and helpful.

3

6x^4 + 15x^3 y^2 + 3x^2 y^3 = 15x^3y^2 + 3x^2y^3 + 6x^4

Added 7/27/2016 9:18:54 PM

This answer has been confirmed as correct and helpful.

(3xy - 1) (4xy + 2) **Weegy:** (3xy - 1) (4xy + 2)
= 12x^2y^2 + 6xy - 4xy - 2
= 12x^2y^2 + 2xy - 2
**User:** [4 - (3c - 1)][6 - ( 3c - 1)] **User:** (a - b)(a 2 + ab + b 2) (More)

Question

Updated 7/27/2016 8:55:04 PM

2 Answers/Comments

(3xy - 1) (4xy + 2) **Weegy:** (3xy - 1) (4xy + 2)
= 12x^2y^2 + 6xy - 4xy - 2
= 12x^2y^2 + 2xy - 2 **User:** (2x - 3y)(4x - y) **Weegy:** (2x - 3y)(4x - y)
= 8x^2 - 2xy - 12xy + 3y^2
= 8x^2 - 14xy + 3y^2 **User:** (x + y + 3)(x + y - 4) **User:** (ab - 9)(ab + 8) **Weegy:** (ab + 3)(ab - 3) = a^2b^2 - 3ab + 3ab - 9; = a^2b^2 - 9 **User:** (m 3 n + 8)(m 3 n - 5) **Weegy:** (n + 8)(n - 2) = n^2 - 2n + 8n - 16; = n^2 + 6n - 16 **User:** (a + 3)(a - 2) **User:** (1 - 7x)(1 + 9x) **User:** (x 2 + 2x - 1)(x 2 + 2x + 5) **Weegy:** (x^2 + 2x - 1)(x^2 + 2x + 5) = x^4 + 2x^3 + 5x^2 + 2x^3 + 4x^2 + 10x - x^2 - 2x - 5; = x^4 + 4x^3 + 8x^2 + 8x - 5 **User:** [4 - (3c - 1)][6 - ( 3c - 1)] **Weegy:** 3-3 = 0 (More)

Question

Updated 7/27/2016 9:01:29 PM

5 Answers/Comments

(x + y + 3)(x + y - 4) = x2 + 2xy + y2 - x - y - 12

Added 7/27/2016 8:58:52 PM

This answer has been confirmed as correct and helpful.

(ab - 9)(ab + 8)

=a^2b^2 + 8ab - 9ab - 72

=a^2b^2 - ab - 72

=a^2b^2 + 8ab - 9ab - 72

=a^2b^2 - ab - 72

Added 7/27/2016 8:59:39 PM

This answer has been confirmed as correct and helpful.

(m^3 n + 8)(m^3n - 5)

=m^6n^2 - 5m^3n + 8m^3n - 40

=m^6n^2 + 3m^3n - 40

=m^6n^2 - 5m^3n + 8m^3n - 40

=m^6n^2 + 3m^3n - 40

Added 7/27/2016 9:00:21 PM

This answer has been confirmed as correct and helpful.

(a + 3)(a - 2)

=a^2 - 2a + 3a - 6

=a^2 + a - 6

=a^2 - 2a + 3a - 6

=a^2 + a - 6

Added 7/27/2016 9:00:49 PM

This answer has been confirmed as correct and helpful.

(1 - 7x)(1 + 9x)

= 1 + 9x - 7x - 63x^2

= - 63x^2 + 2x + 1

= 1 + 9x - 7x - 63x^2

= - 63x^2 + 2x + 1

Added 7/27/2016 9:01:25 PM

This answer has been confirmed as correct and helpful.

32,268,738

questions answered

There are no comments.